Perbandingan Timbulan Sampah Laut dan Daratan di Lokasi Wisata Berbasis Konservasi - Muhammad Irpan Sejati Tassakka; Muhammad Musrianton; Alfi K. Admaja; Indah Alsita; Kezia Gloria Apriliana Runtu; Normayasari (Jurnal Airaha, 2019)
Waha Tourism Community (WTC) is a conservation based tourism and managed by community. The increase of tourist activity is predicted will impact to increase of waste arise. Moreover, the coastal of WTC often gets marine debris that drifts away from other regions at a certain time. The aims of this paper are to know the comparison of waste generation from marine debris and the mainland, also to recommend the alternative of sustainable waste management system in WTC. The measurement of waste arise and composition using the CSIRO method, while the analysis method using IWM2. The results from the research showed that the amount of waste arise from marine debris is more than the mainland with ratio 5:1 (45,8 : 9,1 kg/day). The composition of marine debris consist of 81,6% organics; 5,5% Styrofoams; 3,1% rigid plastics; 3,5% soft plastics; 2,6% metals; 0,4 % glasses; 1,4% rubbers; 0,3% fabrics; 1,1% papers; dan 0,5% another waste. The composition of mainland waste are 63,6% organics, 13,2% rigid plastics; 9,9% soft plastics; 2,2% metals; 2,2 % glasses; 4,1% rubbers; 2,7% papers; and 2,1% another waste. Based on the waste composition in WTC, the most suitable waste management system is the recycling process, biological processing, and bringing the residue to the landfill, which can reduce the air emissions and water pollutions respectively by 1.570.398 gr CO2/year; 1.571.177 gr CH4/year; 34.601.010 gr GWP/year; 7.088 gr BOD/year; 12.146 gr COD/year; and 792 gr SS/year.